2008
DOI: 10.1007/s00213-008-1143-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manipulating progesterone and NMDA receptors in the ventral tegmental area for lordosis of hamsters and rats

Abstract: Rationale-Progesterone (P 4 ) has actions in the ventral tegmental area (VTA) to regulate female sexual behavior in rodents. However, there are few intracellular progestin receptors (PRs) that have been identified in the VTA through which P 4 may have its actions to facilitate lordosis. There are N-methyl-D-aspartate receptors (NMDARs) in the VTA that may be a substrate for P 4 's effects.Objective-We investigated the effects of pharmacologically manipulating NMDARs in the VTA for E 2 -and P 4 -facilitated lor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In particular, pregnane neurosteroids can increase the potency of glutamate and glycine on their cognate receptors (Johansson and Le Grevès 2005; Malayev et al 2002). We have previously demonstrated that intra-VTA blockade of NMDARs can enhance rodent engagement in lordosis (Frye et al 2008a; Petralia et al 2007). The current findings confirm and extend these reports to demonstrate enhanced motivation to engage in copulation, as indicated by increased pacing of sexual contacts among partially ADX rats (commensurate with observations in adrenally intact rats in Table 2) and an increased proportion of MK-801-infused rats engaging in mating compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, pregnane neurosteroids can increase the potency of glutamate and glycine on their cognate receptors (Johansson and Le Grevès 2005; Malayev et al 2002). We have previously demonstrated that intra-VTA blockade of NMDARs can enhance rodent engagement in lordosis (Frye et al 2008a; Petralia et al 2007). The current findings confirm and extend these reports to demonstrate enhanced motivation to engage in copulation, as indicated by increased pacing of sexual contacts among partially ADX rats (commensurate with observations in adrenally intact rats in Table 2) and an increased proportion of MK-801-infused rats engaging in mating compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that DA signaling, but not PR action, in the VTA is required for lordosis (Frye and Vongher, 1999; Sumida et al, 2005), these findings support the idea that PGRMC1 plays a role. However, this is likely to be a complicated story because NMDA signaling in the VTA suppresses lordosis quotients under some circumstances (Frye et al, 2008). Thus, if PGRMC1 is part of the signaling mechanism that controls lordosis, it may be involved in turning off the behavior.…”
Section: Possible Roles For Pgrmc1 In Regulating Rapid Neuroendocrinementioning
confidence: 99%
“…In the VTA, the metabolite of progesterone, 3α,5α‐THP, has actions that facilitate mating (17,18,95,96). 3α,5α‐THP is devoid of affinity for cognate, intracellular PRs, but can have agonist‐like actions at GABA receptors, dopamine type 1‐like receptors (D 1 ), and antagonist‐like actions at NMDA receptors (NMDARs) (8,40,97–100) in the VTA to facilitate mating, as described below.…”
Section: Actions Of Progestogens In the Midbrain Vta Via Nontraditionmentioning
confidence: 99%
“…Midbrain levels of glutamate are increased with progesterone administration (17,18). Antagonising NMDARs via intra‐VTA infusions of MK‐801 or LY235959 enhances progestogen‐facilitated lordosis (99,100). These data indicate that the actions of 3α,5α‐THP in the VTA may occur, in part, through its antagonist‐like actions at NMDARs.…”
Section: Actions Of Progestogens In the Midbrain Vta Via Nontraditionmentioning
confidence: 99%